2002
DOI: 10.1103/physrevb.66.224418
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature evolution of coercivity in nanocrystalline alloys

Abstract: The temperature evolution of the coercivity of a Finemet-type alloy, in which 10 at. % Fe has been substituted by Cr and annealed at different temperatures, has been studied. In the temperature region above the coercivity maximum, the experimental hysteresis loops have been successfully fitted by a combination of two models which use effective field controlled memory effects and temperature rescaling to describe dipolarly interacting superparamagnetic particles. It is shown that the characteristic parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The effect of nanocrystals embedded in the amorphous matrix would be to enhance the entropy change at higher temperatures. 13 Even in the case that the nanocrystals behave as superparamagnetic particles ͑which is the expected situation for small crystalline volume fractions at temperatures above the Curie temperature of the amorphous matrix͒, 23,24 their contribution to the magnetic entropy change would be an enhancement of the signal. 25 Therefore, it is worth mentioning that the reduced crystalline fraction detected by transmission electron microscopy for the alloys with x + y = 1 is not directly evidenced in these results, as MCE does reach zero for this temperature range.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of nanocrystals embedded in the amorphous matrix would be to enhance the entropy change at higher temperatures. 13 Even in the case that the nanocrystals behave as superparamagnetic particles ͑which is the expected situation for small crystalline volume fractions at temperatures above the Curie temperature of the amorphous matrix͒, 23,24 their contribution to the magnetic entropy change would be an enhancement of the signal. 25 Therefore, it is worth mentioning that the reduced crystalline fraction detected by transmission electron microscopy for the alloys with x + y = 1 is not directly evidenced in these results, as MCE does reach zero for this temperature range.…”
Section: Methodsmentioning
confidence: 99%
“…5 This model has been successfully applied to different kind of granular materials, such as Co-Cu alloys, 5 Co nanoparticles embedded in a SiO 2 matrix, 6 and Finemet-type alloys. 7 A remarkable experimental fact is that for superparamagnetic particles with dipolar interaction, the magnetic moment calculated from the Langevin fitting of the anhysteretic magnetization curve does not correspond to the real magnetic moment of the particles. This discrepancy is evidenced by analyzing the thermal dependence of the calculated magnetic moment of a system of thermally stable particles, a moment with an apparent increase with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in coercivity at higher temperatures is associated with the transition to superparamagnetism of the ␣-Fe, Si nanoparticles. It has been shown that this transition is controlled by the dipolar interaction between the particles, both in Finemet 16 and Nanoperm-type 17 nanocrystalline materials. The maximum value of coercivity is related to the effective dipolar interaction field.…”
mentioning
confidence: 99%